Draft Annual Plan 1975-1976 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1975)
Annual Plan 1975-76 - State Outlays and Expenditure Annual Plan 1975-76 Programme-Wise Outlay and Expenditure Union Territory of Pondicherry List of Schemes Included in the Annual Plan. 1975-76 Draft Annual Plan 1975-76-Physical Targets and Developments Scheme-Wise Outlay and Expenditure Centrally-Sponsored Schemes.
Union Territory of Pondicherry Finance and Planning Department